Empirical Evidence on Managerial Ownership, Conservatism, Audit Quality, and Opportunistic Reporting - Hamdani; Hendra Galuh Febrianto; Dhea Zatira; Onesmo Guty (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
This study explores the moderating role of managerial ownership in the relationship between accounting conservatism, leverage, and audit quality on earnings management within Indonesia's raw materials sector. Employing panel data regression with a fixed effects model and Moderated Regression Analysis (MRA), the research analyzes 72 firm-year observations from raw material companies during the 2020–2025 period. The findings reveal that accounting conservatism exerts a significant positive partial effect on earnings management, whereas leverage, audit quality, and all interaction terms with managerial ownership do not demonstrate statistical significance. These results suggest that the influence of governance mechanisms on earnings management is nuanced, with conservatism emerging as the only consistently significant determinant. The absence of significant moderating effects highlights the complexity of managerial ownership's role and cautions against drawing conclusive claims regarding its effectiveness compared to external governance mechanisms. Instead, the study positions managerial ownership as an exploratory dimension that warrants further empirical investigation. By distinguishing statistically supported findings from non-significant tendencies, this research contributes to the literature on corporate governance and earnings management, offering preliminary evidence on governance interactions in Indonesia's raw materials sector and encouraging future studies to refine the analysis with broader samples and alternative methodological approaches.